PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN RUMAH FACIAL NITHA - Dhiyas Vonny Wulan Febriana; Ayu Nurafni Octavia (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
There is a continuous decline in income at Nitha Facial House. Therefore, this research was carried out to increase customer satisfaction which is thought to be influenced by the variables Product Quality, Price and Service Quality. The population used is customers who have visited or used products at Rumah Facial Nitha. Data collected through questionnaires distributed via gform, obtained a sample of 96 people and the analytical tool used was multiple linear regression. This research uses validity tests, reliability tests, and classical assumption tests. The research results show that the Product Quality variable (X1) has an effect on customer satisfaction, based on these results the first hypothesis is accepted. The price variable (X2) influences customer satisfaction, based on these results the second hypothesis is accepted. The Service Quality variable (X3) influences customer satisfaction, based on these results the third hypothesis is accepted. The results of the F test show that the variables Product Quality (X1), Price (X2), Service Quality (X3) together have an influence on Customer Satisfaction (Y), based on these results the fourth hypothesis is accepted. And for the Determination Test (R2) it shows that the Adjusted R Square value in the regression model is 0.857, which means that 85.7% of the Customer Satisfaction variable can be explained by the Product Quality, Price and Service Quality variables. Meanwhile, the remaining 14.3% is explained by other variables outside this research.